PERICLIMENES DENTIDACTYLUS, A NEW DEEP WATER PONTONIINE SHRIMP FROM MAKASSAR STRAIT, INDONESIA - Bruce, A. J. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1984)
A new species of pontoniine shrimp, Periclimenes dentidactylus is described and illustrated. The single specimen was collected from Makassar Strait from over 590 m, a depth exceeded by only two other species of the genus. P. dentidactylus is closely related toÂ F.Â hertwigi Balss, and is probably also an echinoid associate.